Enhancing learning and teaching through student feedback in social sciences - Nair, Chenicheri Sid; Mertova, Patricie, 1975- (Chandos learning and teaching series., 2013)
Student feedback has appeared in the forefront of higher education quality. Of particular relevance are issues of effectiveness and the use of student feedback to improve higher education teaching and learning.